The Improvement of Learning Style on Reading and Interpreting Drug Information obtained from Pharmaceutical Reference Books for the Students of Diploma of Public Health in Pharmacy Technique - สมมาตย์ เจตนิพิฐ; อุยวัฒนกุล พิมพ์ศิริ (Ratchaphruek Journal, 2018)
The objectives of this action research were to 1) investigate problems and needs in the learning management in order to improve reading and interpreting skills for drug information, 2) improve learning activities on reading and interpreting drug information obtained from pharmaceutical reference books, and 3) evaluate the learning effectiveness of the modified learning style. The process could be divided into three phases. In the first phase, current problems and needs toward learning management were studied; the learning style was developed in the second phase. The improved learning style, in the third phase, was then assessed. The sample group comprised of 28 Pharmacy Technique students. The implementation took six months. The instruments utilized were 1) instruments for collecting data consisting of interview guideline, focus group guideline, brainstorming guideline, and pre - posttests; 2) instruments for implementation including lesson plan, course specification, worksheet, reference books such as MIMS, Drug Information Handbook, and Handbook on Injectable Drug, and reading and interpreting drug information workbook. Quantitative analysis included frequency, mean, percentage, standard deviation, minimum, maximum, and paired t-test. Content analysis was employed for analyzing qualitative data. The findings revealed that the current problems on the learning management were teachers lacked a variety of teaching techniques, and students had negative attitude toward English. The modified learning style consisted of 5 stages-adjustment, learning activities, observation, reflection, and assessment-so called ALORA. After implementing the ALORA, the students significantly gained more average score on reading and interpreting skills for drug information (p-value<.0001; 95% CI: 7.31 to 11.76).